2021
DOI: 10.1155/2021/6689698
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Flow Mechanism and Inversion Methods of Fracture Network in Shale Gas Reservoirs

Abstract: The pore structure of shale gas reservoirs has strong heterogeneity, and the flow mechanism in multiscale media is complex. The fracture network of hydraulic fracturing is significantly affected by reservoir in situ stress, rock mechanical properties, and natural fracture distribution. At present, there is no efficient and accurate inversion method for fracture networks. Accurately describing fracture network morphology and flow capacity distribution of induced fracture is an important basis for production ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…The production data analysis method mainly includes an analytical/semi-analytical model and a numerical simulation model (Stalgorova and Mattar, 2012;Huang et al, 2021).…”
Section: Production Data Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The production data analysis method mainly includes an analytical/semi-analytical model and a numerical simulation model (Stalgorova and Mattar, 2012;Huang et al, 2021).…”
Section: Production Data Analysis Methodsmentioning
confidence: 99%
“…However, shale reservoirs have complex mineral composition, natural fractures, and bedding structures. The existing fracture diagnosis technology is not mature enough, and there are problems of low efficiency and poor simulation accuracy, which cannot accurately match the actual fracture network morphology (Huang et al, 2021). Fracture diagnostic technology is the main approach to determine fracture network morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Network in Shale Gas Reservoirs [39], the microunits in the reconstruction area are intercepted, and the physical flow model of orthogonal discrete fracture coupled with dual-media matrix block is established [40]. As shown in Figure 1(b), the fracture network distribution in the actual reservoir reconstruction area is relatively complex, and it is typical as a vertical cross fracture network.…”
Section: Flow Model For Complex Fracturementioning
confidence: 99%
“…Aleksandrov et al (2018) and Wu et al (2017) used this method for fracture analysis. However, with the advancement of technology, it has been found that the error of microseismic monitoring technology is large, and the actual fractures are only between 30% and 70% of the monitoring results (Huang et al, 2021a). The credibility of evaluating fracture channeling using microseismic monitoring can be greatly reduced.…”
Section: Introductionmentioning
confidence: 99%